1977
DOI: 10.1037/0022-0167.24.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to effective cross-cultural counseling.

Abstract: Many mental health professionals have noted that racial and ethnic factors may act as impediments to counseling. Misunderstandings that arise from cultural variations in verbal and nonverbal communication may lead to alienation and/or an inability to develop trust and rapport, An analysis of the generic characteristics of counseling reveals three variables that interact in such a way as to seriously hinder counseling with third-world groups: (a) language variables-use of standard English and verbal communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(188 citation statements)
references
References 36 publications
4
183
0
1
Order By: Relevance
“…On se garde enfin d'être raciste ou ethnocentrique (Turner, 1972) dans ses interventions. Par exemple, de nombreuses recherches démontrent que l'importance accordée à la famille, à la religion, à la verbalisation, au silence, au contact par les yeux, et même aux distances physiques considérées confortables entre les personnes, varie considérablement selon les cultures (Sue et Sue, 1977). On doit donc se garder d'imposer le modèle culturel dominant au sein de ses interventions.…”
Section: Service Socialunclassified
“…On se garde enfin d'être raciste ou ethnocentrique (Turner, 1972) dans ses interventions. Par exemple, de nombreuses recherches démontrent que l'importance accordée à la famille, à la religion, à la verbalisation, au silence, au contact par les yeux, et même aux distances physiques considérées confortables entre les personnes, varie considérablement selon les cultures (Sue et Sue, 1977). On doit donc se garder d'imposer le modèle culturel dominant au sein de ses interventions.…”
Section: Service Socialunclassified
“…Such classroom interactions denigrate culturally diverse students' learning experiences (Blackwell, 2010;Bodycott & Walker, 2000), leave them open to microaggressions from well-meaning faculty and students (Hill, Kim, & Williams, 2010;Rivera et al, 2010;Sue et al, 2007;Watkins, LaBarrie, & Appio, 2010), and pressure them to act as the sole representative of their culture to their classmates (Blackwell, 2010). These classroom interactions also perpetuate the consumer model of cultural learning, in which dominant-culture students learn cultural information without changing their interactive style or developing cultural competency through bidirectional engagement with their culturally diverse classmates (Sue & Sue, 1977). A partial solution to this problem may be to regard the classroom as a collaborative learning community in which psychology professors intentionally learn about the cultures and the culturally specific learning needs of their students and then work to tailor assignments to these students.…”
Section: Acknowledging Rich Cultural Resourcesmentioning
confidence: 99%
“…As Porter and Samovar pointed out, there is maximum cultural distance between 'Asians' and 'Westerners'. They also suggested that there is maximum communication disparity and 14 difficulty between these two cultures (Porter & Samovar, 1988 (Sue, 1977).…”
Section: Cultural Disparity and Communicaton Difficultymentioning
confidence: 99%